The Bilingual Muse : Self-Translation among Russian Poets - Wanner, Adrian, 1960-; Project Muse. (Evanston, Illinois : Northwestern University Press, 2020)
"Examining the work of Elizaveta Borisovna Kul'man, Wassily Kandinsky, Marina Tsvetaeva, Vladimir Nabokov, Joseph Brodsky, Andrey Gritsman, and Katia Kapovich-seven Russian poets of the past two hundred years who self-translated their work-The Bilingual Muse contributes to the rapidly growing field of self-translation studies and sheds light on an overlooked chapter of Russian literary history in a transnational context"--
Introduction "The Trick of Doubling Oneself" -- Elizaveta Kul'man: The Most Polyglot of Russian Poets -- Wassily Kandinsky's Trilingual Poetry -- Marina Tsvetaeva's Self-Translation into French -- Vladimir Nabokov's Dilemma of Self-Translation -- Joseph Brodsky in English -- Self-Translation among Contemporary Russian-American Poets -- Conclusion
Description based on print version record.
Keywords: Self-translation.; Russian poetry; Multilingualism and literature; LITERARY CRITICISM -- General; Autotraduction; Poesie russe -- Traductions -- Histoire et critique; Multilinguisme et litterature; Russian poetry -- 19th century -- History and criticism; Russian poetry -- 20th century -- History and criticism; Self-translation.; Russian poetry -- Translations -- History and criticism; Multilingualism and literature; Critiques litteraires; Literary criticism; Criticism, interpretation, etc; Literary criticism; Electronic books